ECHNOLOGICAL PROVISIONING OF TEST CONTROL OF SPECIAL HEALTH GROUP STUDENTS’ POWER ABILITIES - V.M. Koryahin; O. Z. Blavt (Physical Education of Students)
Purpose: to substantiate and realize modern electronic technological means for perfection of test control of students’ power abilities in special health groups. Material: materials of students’ test control have been used in the research. Results: we have developed electronic system for test monitoring of students’ power abilities. Besides, we showed possibilities of innovative automated methodic application for test monitoring of students’ power abilities. Strict regulation of monitoring significantly decreases dispersion of error and raises reliability of test. The mentioned monitoring system removes dependence of result on teacher’s subjective perception of information. Conclusions: Implementation of the offered system of monitoring of students’ power abilities’ functional state ensures promptness of confident testing results’ reception. It will facilitate effectiveness of control in students’ physical education.